2023
DOI: 10.1017/awf.2023.10
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strategic ventilation adjustments on stress responses in horses housed full-time in a vector-protected barn during the African horse sickness outbreak in Thailand

Abstract: The severe outbreak of African horse sickness (AHS) in Thailand has forced horses to reside full-time inside barns that are covered by a small mesh net to prevent minuscule AHS insect vectors from gaining access. However, housing in the net-covered barn induces stress in horses, which compromises their welfare. Implementing strategic airflow adjustment while retaining the vector-protection characteristics has been proposed to help alleviate this problem. The present study aimed to investigate the effect of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A difference in air-conditioning settings could explain this disparity. It has been reported that the relative humidity was significantly higher within a closed barn than in an outside barn [29, 30]. Likewise, the moisture production becomes pronounced, causing increased relative humidity in a closed-door, air-conditioned room of a human dwelling [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A difference in air-conditioning settings could explain this disparity. It has been reported that the relative humidity was significantly higher within a closed barn than in an outside barn [29, 30]. Likewise, the moisture production becomes pronounced, causing increased relative humidity in a closed-door, air-conditioned room of a human dwelling [31].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may indicate, in part, that the N-ATS condition created more stress than the others. Cortisol levels are modulated by the circadian rhythm, peaking in the morning and then gradually reducing [29, 30, 32, 33]. Since our experiments were initiated in the morning and ended in the afternoon, it could be that increases in cortisol levels after transport were not under circadian rhythm but external stimuli from the transports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results reflect the enormous stress on the ponies during highintensity exercise in the chukkas. However, a further decrease in cortisol levels (below the baseline) at 120-180 minutes may result from the hormone's circadian rhythm during the late evening [22,[56][57][58][59].…”
Section: Plos Onementioning
confidence: 99%